The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/ffunb.2023.1086194
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mycobiome and arbuscular mycorrhizal fungi associated with the rizosphere of the genus Inga in the pristine Ecuadorian Amazon

Abstract: This study explored the composition of the mycobiome in the rhizosphere of Inga seedlings in two different but neighboring forest ecosystems in the undisturbed tropical Amazon rainforest at the Tiputini Biodiversity Station in Ecuador. In terra firme plots, which were situated higher up and therefore typically outside of the influence of river floods, and in várzea plots, the lower part of the forest located near the riverbanks and therefore seasonally flooded, tree seedlings of the genus Inga were randomly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
2
0
0
1
Order By: Relevance
“…It is remarkable that we found an extremely low abundance of AMF, which might be explained in two ways: (1) Inga , in general, is associated with very low abundances of AMF. This was reported by Arévalo‐Granda et al (2023) in an extensive study, who found only 1.42% Glomeromycotina (specifically Glomeraceae and Acaulosporaceae) in Ecuadorian Amazon Inga rhizosphere. Also, edaphic factors such as pH, water content, and density, among others, may determine AMF richness (Arévalo‐Granda et al 2023), which may explain the general trend of our seedlings forming lower associations with AMF in these specific field conditions.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It is remarkable that we found an extremely low abundance of AMF, which might be explained in two ways: (1) Inga , in general, is associated with very low abundances of AMF. This was reported by Arévalo‐Granda et al (2023) in an extensive study, who found only 1.42% Glomeromycotina (specifically Glomeraceae and Acaulosporaceae) in Ecuadorian Amazon Inga rhizosphere. Also, edaphic factors such as pH, water content, and density, among others, may determine AMF richness (Arévalo‐Granda et al 2023), which may explain the general trend of our seedlings forming lower associations with AMF in these specific field conditions.…”
Section: Discussionsupporting
confidence: 59%
“…This was reported by Arévalo‐Granda et al (2023) in an extensive study, who found only 1.42% Glomeromycotina (specifically Glomeraceae and Acaulosporaceae) in Ecuadorian Amazon Inga rhizosphere. Also, edaphic factors such as pH, water content, and density, among others, may determine AMF richness (Arévalo‐Granda et al 2023), which may explain the general trend of our seedlings forming lower associations with AMF in these specific field conditions. (2) We may not have detected some of the AMF diversity given that our main goal was focused on microbial diversity in general, not only AMF.…”
Section: Discussionsupporting
confidence: 59%
“…( gênero Inga são reconhecidas por sua eficácia na fixação de nitrogênio devido à sua simbiose com bactérias que colonizam nódulos radiculares, denominadas rizóbios (Rhem et al, 2021;Arévalo-Granda et al, 2023;Velasco-Trejo et al, 2023). I. vera e P. dubium são consideradas espécies-chave em processos de recuperação de áreas degradadas, pois apresentam crescimento rápido, adaptabilidade às diferentes condições de solo e potencial para estocagem de carbono na biomassa, contribuindo para a mitigação das mudanças climáticas (Balestrin et al, 2021, Albuquerque et al 2022Silva et al, 2023).…”
Section: Parâmetros Fitossociológicos E Estoque De Carbonounclassified